Biochemical transformation of mouse cells by herpes simplex virus type 2: enhancement by means of low-level photodynamic treatment - Verwoerd, D W; Rapp, F (Journal of virology, 1978)
The biochemical transformation of thymidine kinase-deficient cells by UV-inactivated herpes simplex virus is enhanced by low-level photodynamic treatment of the infected cells. At the concentration of proflavine used, the virus was not inactivated and both virus and cellular DNA syntheses were only marginally inhibited. The observed enhancement of the transfer of a virus gene to the cell genome suggests a possible cocarcinogenic role for photodynamically active dyes at very low concentrations.